2015
DOI: 10.1016/j.neurobiolaging.2014.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant adenoassociated virus 2/5-mediated gene transfer is reduced in the aged rat midbrain

Abstract: Clinical trials are examining the efficacy of viral vector-mediated gene delivery for treating Parkinson’s disease (PD). While viral vector strategies have been successful in preclinical studies, to date clinical trials have disappointed. This may be due to the fact that preclinical studies fail to account for aging. Aging is the single greatest risk factor for developing PD and age alters cellular processes utilized by viral vectors. We hypothesized that the aged brain would be relatively resistant to transdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…Numerous considerations, in addition to interspecies scaling, have to be made when translating rodent studies into the NHP and, ultimately, humans. For instance, we have established that age is an important covariate in transduction efficiency, where certain serotypes exhibit deficiencies in distinct anatomical locations 5, 49. Thus, age-matching experimental subjects in preclinical testing is increasingly important.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous considerations, in addition to interspecies scaling, have to be made when translating rodent studies into the NHP and, ultimately, humans. For instance, we have established that age is an important covariate in transduction efficiency, where certain serotypes exhibit deficiencies in distinct anatomical locations 5, 49. Thus, age-matching experimental subjects in preclinical testing is increasingly important.…”
Section: Discussionmentioning
confidence: 99%
“…Additional considerations that may warrant the use of one serotype over another is whether a patient has pre-existing immunity to a specific serotype. Moreover, various serotypes are differentially impaired in the aged brain 5, 49. Finally, the increased efficacy of these vectors would also allow the use of lower titers, thereby lowering the risk of an immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Our group recently found that rAAV2/5-GFP transduction in the SN is reduced in aged animals compared to young animals [82], but other studies have shown that rAAV2/9-tau and -GFP transduction is unaffected in the SN [83, 84]. The differences in transduction efficiency with age may reflect the use of different rAAV serotypes.…”
Section: Advantages Of Viral Vector Systemsmentioning
confidence: 99%
“…Many of these studies were done using either glial cell lines or in young animals, neglecting the impact of the pro-inflammatory actions of α-syn within the primed glial environment of an aging brain, thus causing even more damage. In fact, when α-syn is introduced into an aged animal it is more cytotoxic compared to the young controls [34]. …”
Section: Role Of Neuroinflammationmentioning
confidence: 99%